The english teaching learning process through critical thinking development with the students of eighth level at “Luis Fernando Ruiz” educative unit during the academic cycle april-august 2015 - Fabara Quintana, Johana Carolina (2015)
This research work was focused on developing critical thinking in students at "Luis Fernando Ruiz" Educative Unit, located in the Latacunga city. The educative unit has a highly qualified education however; at present, the development of critical thinking is not being taken with the importance that it deserves from the authorities and teachers of the institution. Students are habituated to repeat without giving response or criterion from their own thinking. That`s why, this research has as an objective to develop critical thinking in the students in the English language. It was focused on providing a module which help and guide teachers and students in the teaching and learning process to develop the ability to think critically. It permitted to develop classes in a dynamic and funny way, using strategies and activities to develop each skill….